Peran Promosi Nilai Pelanggan Terhadap Keputusan Pembelian di Indomaret - Hartono, Ardhit Wiro; Putra, Viko Rachmatullah (CV ODIS, 2025)
Promotion is one of the key factors influencing sales activities conducted by companies. It is a mandatory strategy used to market and sell products to consumers. Various promotional strategies are implemented to attract consumer interest. This research discusses the role of customer value promotion in purchasing decisions at Indomaret. This study employs a quantitative method with a survey technique, using a random sampling approach with 40 Indomaret consumers. The data was collected through questionnaires. The results indicate that customer value promotion significantly influences purchasing decisions at Indomaret.